The Effect of E-Commerce Implementation in the Curriculum on Students’ Entrepreneurship Interest - Azizah - Azizah; Isnaini - Nurkhayati; Sandi - Supaya; Noor - Suroija; Jumi - Jumi (Politeknik Negeri Semarang, 2022)
In modern era, the use of e-commerce in everyday life is inseparable, especially among millennials, both in the world and in Indonesia, which is one of the most fertile e-commerce market shares. E-commerce make many new entrepreneurs have emerged, especially among the younger generation. Students as the young generation, should be the pioneers of the emergence of new entrepreneurs. The purpose of this study was to measure the influence of the application of e-commerce in increasing student interest in entrepreneurship, to find out what factors were driving and inhibiting students in entrepreneurship using e-commerce media and to create a model for evaluating curriculum that contributed to the application of e-commerce in increasing student entrepreneurial interest. The results of the research conducted showed that the independent variable (X), E-commerce, affected the dependent variable, interest in entrepreneurship (Y) by 68.8%. Based on this, the success of the E-Commerce course in influencing the interest in entrepreneurship still needs to be improved. This can be done by providing the right learning model. Appropriate modeling is expected to increase the influence of student entrepreneurial interests after receiving e-commerce courses.